Synthesis of Citrate-Capped Gold Nanoparticles from Reduced [AuCl4]– on Ascorbic Acid-Immobilized Mg/Al Hydrotalcite - Agustina Sus Andreani; Suyanta Suyanta; Eko Sri Kunarti; Sri Juari Santosa (Universitas Gadjah Mada, 2018)
Reductive adsorption of [AuCl4]-– by using ascorbic acid immobilized on Mg/Al hydrotalcite (Mg/Al HT) and synthesis of gold nanoparticles (AuNPs) from the reduced gold using sodium citrate have been conducted. Mg/Al HT was synthesized by co-precipitation method at pH 10 with molar ratio of Mg(II) and Al(III) 2:1. Ascorbic acid (AA) was then immobilized on Mg/Al HT to form hybrid of AA and Mg/Al HT (Mg/Al HT-AA). Mg/Al HT-AA was used to reductively adsorb [AuCl4]– and the formed Au(0) was extracted by using sodium citrate to form citrate-capped AuNPs. The formation of AuNPs from 100 mg/L [AuCl4]– solution removed by 60 mg Mg/Al HT-AA was optimum at pH 5.0, by using 70 mM sodium citrate and 2 h sonication time. This optimum condition was successfully applied to synthesize AuNPs from [AuCl4]– as the leaching product of gold from PCB using aquaregia.